BluB/CobT2 fusion enzyme activity reveals mechanisms responsible for production of active form of vitamin B(12) by Propionibacterium freudenreichii - Deptula, Paulina (Microb Cell Fact, 2015)
BACKGROUND: Propionibacterium freudenreichii is a food grade bacterium that has gained attention as a producer of appreciable amounts of cobalamin, a cobamide with activity of vitamin B(12). Production of active form of vitamin is a prerequisite for attempts to naturally fortify foods with B(12) by microbial fermentation. Active vitamin B(12) is distinguished from the pseudovitamin by the presence of 5,6-dimethylbenzimidazole (DMBI) as the lower ligand. Genomic data indicate that P. freudenreichii possesses a fusion gene, bluB/cobT2, coding for a predicted phosphoribosyltransferase/nitroreductase, which is presumably involved in production of vitamin B(12). Understanding the mechanisms affecting the synthesis of different vitamin forms is useful for rational strain selection and essential for engineering of strains with improved B(12) production properties. RESULTS: Here, we investigated the activity of heterologously expressed and purified fusion enzyme BluB/CobT2. Our results show that BluB/CoBT2 is responsible for the biosynthesis of the DMBI base and its activation into α-ribazole phosphate, preparing it for attachment as the lower ligand of cobalamin. The fusion enzyme was found to be efficient in metabolite channeling and the enzymes’ inability to react with adenine, a lower ligand present in the pseudovitamin, revealed a mechanism favoring the production of the active form of the vitamin. P. freudenreichii did not produce cobalamin under strictly anaerobic conditions, confirming the requirement of oxygen for DMBI synthesis. In vivo experiments also revealed a clear preference for incorporating DMBI over adenine into cobamide under both microaerobic and anaerobic conditions. CONCLUSIONS: The herein described BluB/CobT2 is responsible for the production and activation of DMBI. Fusing those two activities results in high pressure towards production of the true vitamin B(12) by efficiently activating DMBI formed within the same enzymatic complex. This indicates that BluB/CobT2 is the crucial enzyme in the B(12) biosynthetic pathway of P. freudenreichii. The GRAS organism status and the preference for synthesizing active vitamin form make P. freudenreichii a unique candidate for the in situ production of vitamin B(12) within food products. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0363-9) contains supplementary material, which is available to authorized users.